Protection of the Rights of Elderly Prisoners at Class II A Sidoarjo Correctional Institution - Zahroh, Milltuz; Dwi Miarsa, Fajar Rachmad; Yahya, Dhofirul (Dinasti Research, 2025)
Protection of elderly prisoners or what we often call the elderly is one of the issues that should receive special attention in criminal justice in Indonesia. From a legal perspective, these elderly prisoners are often in physical or psychological conditions that require fair treatment because it is influenced by their rights as Indonesian citizens. The legal and correctional system in Indonesia has regulated several provisions regarding elderly convicts. As regulated in Law No. 12 of 1995 concerning Corrections. One of them is the rights of prisoners in general, but cannot explicitly address the problems being faced by elderly prisoners. However, existing regulations must be able to provide guarantees for the basic rights that elderly prisoners must obtain. Such as, the right to receive health and medical care, the right to feel safe from discrimination and the right to their safety while serving their sentence. From a juridical perspective, attention to the protection of human rights (HAM) for elderly prisoners is very important. In accordance with the principle of protecting human rights contained in the constitution and many national instruments, it emphasizes the importance of humane treatment, including for elderly prisoners. However, in its implementation, elderly convicts often have difficulties when they are in correctional institutions